Pertanggungjawaban Pidana terhadap Pelaku Penghinaan Partai Politik - I Komang Giri Maharta; I Gusti Bagu Suryawan; Ni Made Sukaryati Karma (Warmadewa Press, 2021)
Insult to political parties in Indonesia can cause serious problems if not dealt with legally. self-interest and bad political practice will provoke humiliation for party political opponents. Every political party must be a legal entity so that it is not easy to overthrow one of the political parties. This study examines the punishment arrangements for insulting political parties and analyzes the criminal responsibility associated with insulting political parties. This study was designed using normative research with an approach to statutory problems related to insulting acts against political parties. Sources of legal materials were primary and secondary data obtained through recording and documentation techniques. The results showed that the regulation of humiliation of political parties is made in order to achieve a sense of security and can protect those who are the object of humiliation. Insult can be said to be a criminal act because it violates the law that can be done intentionally or unintentionally. There must be accountability for these acts based on applicable law and declared as an act that is punishable by imprisonment or a fine as stipulated in Article of the Criminal Code. 207.